(untitled) (Journal of Universal Science Research, 2025)
This article examines the linguocultural and social dimensions of Dr. Seuss’s children’s literature, focusing on how imaginative language conveys complex themes such as racial equality, environmentalism, and authoritarianism. Through qualitative analysis of The Sneetches, The Lorax, and Yertle the Turtle, the study highlights how stylistic devices like rhyme, metaphor, and neologisms serve as semiotic tools for moral and cultural instruction. The research underscores the pedagogical and discursive power of children’s literature in shaping young readers’ ethical and cognitive development within broader sociolinguistic contexts.